ETOS DAN PANDANGAN HIDUP KOMUNITAS NELAYAN BUGIS DALAM KEHIDUPAN SOSIAL EKONOMI (STUDI KASUS DI KELURAHAN TONDONGGEU KECAMATAN ABELI KOTA KENDARI PROVINSI SULAWESI TENGGARA) - La Janu (Forum Ilmu Sosial)
This research is aimed to know the concept of â€œtellutummasarangâ€ and â€œduatemmalessengâ€ as asystem of culture added in ethos and way of life Buginese fi sherman at Tondonggeu Village chife, KendariTown. The function and effect of ethos and that way of life in moving ethos principles and way of lifedue to ethos social dynamic and cultural moving wich is happen while to day. The data in this study wascollected by observation and interview. The design of this study was descriptive qualitative. Tehis studyshowed a few study. First, to carry out social life, Buginese fi sherman in this area based or ethos andway of life are called â€œtellutemmasarangâ€ and â€œduatemmalessengâ€. Second, in ethos and way of life areknow that natural as integral part from human, so natural structure is refl ected on social structure, socialstratifi cation and economy structure. Third, by ethos and way of life, in fulfi llment their social economyneeds, Buginese fi sherman have a high work ethos and as if they are never tired. Fourth, the principleof behavior and attitude in social connection integrally and interdependence, it appears has been moved,together with social dynamic process and cultural changing which is happen in modernity era. Key words: Ethos, way of life, social economy